2016
DOI: 10.1007/s11255-016-1460-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma: applicability of the apparent coefficient of the diffusion-weighted estimated by MRI for improving their differential diagnosis, histologic subtyping, and differentiation grade

Abstract: The data received in our study demonstrate a substantial restriction of diffusion of hydrogen molecules in tissues of ccRCC in comparison with the healthy renal parenchyma preconditioned by the greater density of tumor. A statistically significant difference in mean ADC values of ccRCC with different grades of nuclear pleomorphism by Fuhrman was observed: Low-grade tumors showed higher mean ADC values compared to high-grade tumors. The modality of the MRI DWI along with ADC measurement allows to reliably diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
2
18
0
3
Order By: Relevance
“…Previous studies applying DWI to evaluate kidney tumour type concluded that kidney lesions generally have a lower ADC than normal kidney tissue [ 13 , 17 , 29 ] and some studies also found a higher mean ADC value in benign lesions than in malignant lesions [ 15 , 30 , 31 ]. Studies typically find a higher ADC in oncocytomas than in RCCs [ 12 15 , 17 , 30 32 ] and therefore, ADC is likely to be a valuable parameter in evaluating tumour type.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies applying DWI to evaluate kidney tumour type concluded that kidney lesions generally have a lower ADC than normal kidney tissue [ 13 , 17 , 29 ] and some studies also found a higher mean ADC value in benign lesions than in malignant lesions [ 15 , 30 , 31 ]. Studies typically find a higher ADC in oncocytomas than in RCCs [ 12 15 , 17 , 30 32 ] and therefore, ADC is likely to be a valuable parameter in evaluating tumour type.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that decreasing ADC values are found with increasing Fuhrman grade. This may be helpful in detecting high-grade ccRCCs [54,61].…”
Section: Differentiation Of Subtypes Clear Cell Rccmentioning
confidence: 99%
“…Our previous publications demonstrated high efficacy of the measuring of apparent diffusion coefficient of DWI. Its applica tion as the radiological biomarker of RCC allows to diagnose this pathology accurately and correctly as well as to carry out its differentiation from the benign kidney lesions avoiding the application of contrast substances [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…За даними EAU така мо дальність МРТ, як дифузійно зважені зображення (ДЗЗ) володіє потенціалом для диференційної діаг ностики НКР [6], проте у жодному з досліджень не було наведено даних, достатніх для використання променевих біомаркерів НКР на основі МРТ зобра жень в широкій медичній практиці [29][30][31][32]. У наших попередніх публікаціях нами була продемонстрова на висока ефективність застосування вимірюваного коефіцієнта дифузії ДЗЗ МРТ у якості променевого біомаркеру НКР, що дозволяло не тільки достовірно діагностувати дану патологію, але й проводити її ди ференціацію з доброякісними нирковими новоутво реннями, уникаючи використання контрастних ре човин [33,34].…”
Section: Introductionunclassified